1988
DOI: 10.1002/art.1780310710
|View full text |Cite
|
Sign up to set email alerts
|

Radial and spinal bone mineral density in a patient population

Abstract: Density of the radius (by single-photon absorptiometry) and the spine (by dual-photon absorptiometry) was measured in 281 normal young women and in a large heterogenous group of 1,622 consecutive female patients. Both spinal and radial density were useful measurements when performed on patients with medical indications; spine and radius densities in these patients averaged 1620% below those of age-matched controls. However, patients younger than 60 years of age had deficits of spine density that were twice as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 25 publications
2
8
0
1
Order By: Relevance
“…The T-score decrease after age 50 years is very similar to that reported by Mazess et al [16] and Rey et al [26]. In the patient population of Mazess et al [16] osteopenic levels were reached at ages 52-55 years and osteoporosis at around age 75 years. At the distal forearm Rey et al [26] found a T-score reduction of -3.0 SD between 30 and 75 years of age.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The T-score decrease after age 50 years is very similar to that reported by Mazess et al [16] and Rey et al [26]. In the patient population of Mazess et al [16] osteopenic levels were reached at ages 52-55 years and osteoporosis at around age 75 years. At the distal forearm Rey et al [26] found a T-score reduction of -3.0 SD between 30 and 75 years of age.…”
Section: Discussionsupporting
confidence: 87%
“…In our total sample the prevalence of osteoporosis is 15.16% and in the age groups 50 years and over (6221 women) it is 20.45%. We compared our results with those of studies based on patient populations referred for forearm bone density testing [11,15,16]. In a sample of 1622 consecutive female patients Mazess et al [16] found osteoporosis defined as BMD values 430% lower than those of young healthy premenopausal females in 2-3% of all women aged 30-49 years, in 16% between 50 and 59 years, in 34% between 60 and 69 years, in 56% between 70 and 79 years, and in 62% between 80 and 89 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, as proporções entre osso cortical e trabecular sofrem variações significativas, dependendo do modo de aplicação das técnicas utilizadas, o que pode comprometer a precisão e a reprodutibilidade das medidas obtidas no rádio [13][14][15] . Outro aspecto a ser assinalado é o fato de diferentes autores [14][15][16] terem observado baixa correlação entre as densidades ósseas medidas no terço proximal e/ou distal do rádio com a coluna e a região proximal do fêmur. Da mesma forma, Aloia et al 16 , em 1990, ao estudarem mulheres saudáveis, também não encontraram correlação entre a densidade óssea do terço distal do rádio e o conteúdo do cálcio corporal total.…”
Section: Discussionunclassified
“…A technique that measures information regarding both the mass and micro-architecture of bone should therefore provide the most accurate assessment of fracture risk. Currently, however, no such validated technique exists and a measurement of bone mass alone has been shown to be the single most important determinant of fracture risk [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%